Implementation of a Healthcare of Elderly Course With Multi-Professional Teachers for Undergraduate Medical Students in a Public University in Malaysia—A Quasi-Experimental Pre and Post Study - Ng, Zhi Ling; Mat Din, Hazwan; Zakaria, Nor Fadhlina; Inche Mat, Liyana Najwa; Wan Zukiman, Wan Zul Haikal; Md Shah, Anim; Daut, Ummi Nadira; Sallehuddin, Hakimah Mohammad (Frontiers in Public Health, 2021)
Clinical practise in the ageing population is changing from organ-specific specialty care to holistic care. This is done through comprehensive geriatric assessment and multi-disciplinary team management. Hence, we adopted an approach consisting of multi-professional teachers teaching a Healthcare of Elderly Course (HEC), in a public university in Malaysia. We aimed to analyze the students' attitude, self-perceived competency and interest in geriatric medicine as a career before and after the course. We also investigated variables that might influence this interest among these students. All 96 students in the course were invited to participate in the survey. Sixty-eight (70.8%) completed both pre and post-course questionnaires. Although most students (93%) have a positive attitude (University of California at Los Angeles Geriatric Attitude Scale >3) toward older adults at baseline, it did not significantly increase post-course. We found that the mean scores for self-perceived competency increased from 3.62 (±0.76) to 3.81 (±0.56) post-course (p < 0.01). However, the students remained neutral with no significant change in the mean interest in pursuing a geriatric medicine career after the course. Students with higher self-perceived competency post-course were found to be more interested in geriatric medicine (β = 0.56, p < 0.001). In conclusion, the HEC in our centre could sustain a positive attitude and increase self-perceived competency in students. It is important to increase the preparedness of our graduates in managing older adults with frailty and multimorbidity. Future studies may involve inter-professional education of students from multiple disciplines undergoing the same course to nurture real-life collaborations in managing the ageing population.